2015
DOI: 10.1016/j.dsr.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of mesoscale eddies in transport of Fukushima-derived cesium isotopes in the ocean

Abstract: We present the results of in-situ measurements of 134 Cs and 137 Cs released from the Fukushima Nuclear Power Plant (FNPP) collected at surface and different depths in the western North Pacific in June and July 2012. It was found that 15 month after the incident concentrations of radiocesium in the Japan and Okhotsk seas were at background or slightly increased level, while they had increased values in the subarctic front area east of Japan. The highest concentrations of 134 Cs and 137 Cs up to 13.5 ± 0.9 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…It originated in the beginning of February 2012 with the center at around 41.9 • N, 148 • E and captured some contaminated water from the HE. The TsE was sampled in the R/V Professor Gagarinskiy cruise on 5 July, 2012, and found to have concentrations of 137 Cs and 134 Cs over the background level at the surface and at intermediate depths (Budyansky et al, 2015). All these eddies will be studied in this section from the Lagrangian point of view in order to simulate and track by which transport pathways they could have gained water masses from the Fukushima area or from other origins and to compare qualitatively the simulation results with in situ measurements.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It originated in the beginning of February 2012 with the center at around 41.9 • N, 148 • E and captured some contaminated water from the HE. The TsE was sampled in the R/V Professor Gagarinskiy cruise on 5 July, 2012, and found to have concentrations of 137 Cs and 134 Cs over the background level at the surface and at intermediate depths (Budyansky et al, 2015). All these eddies will be studied in this section from the Lagrangian point of view in order to simulate and track by which transport pathways they could have gained water masses from the Fukushima area or from other origins and to compare qualitatively the simulation results with in situ measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The Kumamoto et al, 2014) with measured radiocesium concentrations at the background level (the green diamonds) and with higher concentration levels (the magenta diamonds). (b-d) The Lagrangian maps show evolution of the Tsugaru eddy (TsE), which originated on 4 February 2012 (a) after splitting of the HE and was sampled by Budyansky et al (2015) at station 84 on 5 July 2012 and shown to have increased radiocesium concentrations (the magenta diamond in d).…”
Section: The Hokkaido Eddymentioning
confidence: 99%
See 3 more Smart Citations